2022
DOI: 10.1186/s43042-022-00262-4
|View full text |Cite
|
Sign up to set email alerts
|

Hematological indices in pediatric patients with acyanotic congenital heart disease: a cross-sectional study of 248 patients

Abstract: Background Congenital heart disease CHD is a significant cause of mortality and morbidity in children worldwide. Patients with congenital heart disease may develop hematological problems, including thrombocytopenia and neutropenia. In addition, several studies indicate the higher frailty of patients with CHDs to infections and malignancies. Nevertheless, the mechanisms of immune system changes in these patients have remained in the shadow of uncertainty. Moreover, very few studies have worked o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…Additionally, nearly half of the children had mixed CHD problems; therefore, this might exaggerate the prevalence of anemia in our finding. Relatively, our finding is equivalent or relatively similar finding with the studies by Mohammadi et al and Gaiha et al with a prevalence of 18.18% and 19.3% [ 16 , 20 ]. However, iron deficiency anemia is reported to be common in individuals with CCHD even in the presence of high hematocrit levels.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, nearly half of the children had mixed CHD problems; therefore, this might exaggerate the prevalence of anemia in our finding. Relatively, our finding is equivalent or relatively similar finding with the studies by Mohammadi et al and Gaiha et al with a prevalence of 18.18% and 19.3% [ 16 , 20 ]. However, iron deficiency anemia is reported to be common in individuals with CCHD even in the presence of high hematocrit levels.…”
Section: Discussionsupporting
confidence: 92%
“…This explanation strengthen by the study conducted in India showed that hemoglobin and hematocrit levels and RBC count were paradoxically higher in the CCHD as compared to the healthy controls [ 21 ]. Regarding the ACHD cases, the prevalence of anemia in our study was equivalent to that found in studies conducted by Mohammadi et al and Gaiha et al [ 16 , 20 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with previous research, which has demonstrated a potential correlation between Ventricular Septal Defect (VSD) and neutropenia. 3 Additionally, we unraveled the well-documented association of cirrhosis and HCV infection with leukopenia, attributed to the toxic effects of HCV and alterations in the bone marrow microenvironment influencing stem cell differentiation. 4 Furthermore, our study recognized the potential significance of identifying hematological malignancy in the context of autoimmune diseases, particularly rheumatoid arthritis (RA).…”
Section: Discussionmentioning
confidence: 96%
“…Congenital heart disease (CHD) is the most common developmental anomaly (4 -10 per 1,000 live births), representing an important noninfectious cause of death in children. Patients with CHD are at higher risk of infections (1). Many of them will undergo cardiac surgery, whose outcomes depend on many preoperative, intraoperative, and postoperative factors.…”
Section: Introductionmentioning
confidence: 99%